2014
DOI: 10.1590/s1807-76922014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on actor-network theory, governance networks, and strategic outcomes

Abstract: In an attempt to instigate discussion in the areas of organizational studies and strategy, this essay focuses on themes related to Governance, Actor-Network Theory, and Strategic Outcomes. We seek to expand understanding of the Governance Network Theory by proposing the inclusion of human and non-human actors from the Actor-Network Theory in its scope. Recent studies concerning the notion of heterogeneous networks have demonstrated the importance of non-human actors for understanding social and organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 27 publications
(57 reference statements)
0
27
0
4
Order By: Relevance
“…we found that, through hybrid relationships of certain central actants with other human and non-human actors, networks and relationships are being created in an intense process of overcoming interest conflicts (Montenegro & Bulgacov, 2014). Through the four stages of the translation process, the problems to be faced and the objectives to be achieved are exposed; the main actors and their interests are identified; the attribution and roles of each element are outlined; and the allies are mobilized to then form networks among the actants in the field of specialized accounting inspection.…”
Section: Relationships In Specialized Accounting Inspection From the mentioning
confidence: 94%
See 3 more Smart Citations
“…we found that, through hybrid relationships of certain central actants with other human and non-human actors, networks and relationships are being created in an intense process of overcoming interest conflicts (Montenegro & Bulgacov, 2014). Through the four stages of the translation process, the problems to be faced and the objectives to be achieved are exposed; the main actors and their interests are identified; the attribution and roles of each element are outlined; and the allies are mobilized to then form networks among the actants in the field of specialized accounting inspection.…”
Section: Relationships In Specialized Accounting Inspection From the mentioning
confidence: 94%
“…The human and non-human actors in relationships, according to Montenegro and Bulgacov (2014), are equally relevant, and should be considered in the process of social study and investigation. In the sphere of the specialized accounting inspection, the human actors, represented by the accounting expert, expert's assistant, judge and courts, are the main actants of the relationships, acting in the design of networks.…”
Section: Human and Non-human Actants In Specialized Accounting Inspecmentioning
confidence: 99%
See 2 more Smart Citations
“…The Actor-Network Theory enables the analysis or the interrelationship between the technical choice and the social destiny of the innovations, through the point of view of different entities that surround the human, non-human, technical and social world. Another important factor is mentioned by Montenegro and Bulgacov (2014), when they state that actors are constantly involved with each other in the formation and the destruction of groups and in their attempt to provide explanations to their actions.…”
Section: Actor-network Theorymentioning
confidence: 99%